Consumer Perception and Patronage of Nigerian-Made Consumer Electronics (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
In Nigeria, locally manufactured consumer electronics face low patronage due to consumer perceptions regarding value, risk, quality, and innovativeness, despite government initiatives promoting domestic products, with imported alternatives dominating the market, highlighting the need to understand the psychological and behavioral determinants of local product adoption. This study examines the influence of consumer perception on the patronage of Nigerian-made electronics, aiming to identify factors that encourage initial purchase, actual purchase behavior, and repurchase intention. A descriptive quantitative research design was employed, targeting adults aged 18 years and above residing in Surulere, Lagos State, with a sample of 305 respondents selected using convenience sampling. Data were collected via structured questionnaires measured on a five-point Likert scale and analyzed using SPSS, incorporating descriptive statistics and linear regression to examine relationships between perception dimensions and patronage outcomes. Results indicate that perceived value positively and significantly influences patronage intention (β = 0.358, p < 0.001), perceived risk negatively affects actual purchase behavior (β = -0.290, p < 0.001), and perceived quality positively predicts repurchase intention (β = 0.346, p < 0.001), demonstrating that consumer perceptions play a pivotal role in both initial and repeat patronage of Nigerian-made electronics. The study concludes that enhancing perceived value, mitigating perceived risk, and maintaining consistent product quality are critical strategies for increasing adoption and loyalty, and recommends that manufacturers implement value-based marketing, robust after-sales support, and continuous quality improvement, while policymakers should support initiatives that promote domestic products and build consumer confidence.